Challenges of Deaf Students in Online Learning at Universities - Imam Yuwono; Mirnawati Mirnawati; Dewi Ekasari Kusumastuti; Tenty Jahrina Ramli (STAI Hubbulwathan Duri, 2022)
This study describes the challenges faced by deaf students in online learning, focusing on three aspects: internet access and use of media, volunteer assistance, and interaction in online learning. This study uses a qualitative approach with a descriptive method. Sources of data in this study were deaf students and volunteers. Data collection techniques using interviews and observation. Data were analyzed using Miles and Huberman's interactive data analysis model, which consisted of data reduction, presentation, and conclusion drawing. The results of the study describe that 1) deaf students have problems with internet networks and quotas so that they are not optimal in attending lectures, besides that deaf students also experience problems in using learning media used in lectures, for example, in using zoom, and e-learning SIMARI, students Deaf people still have difficulty using some of the features contained in e-learning. 2) volunteers who are tasked with assisting deaf students are active students. The practice of mentoring is not optimal because volunteers also learn from their homes. In addition, the distance between the houses of deaf students and volunteers is quite far, and some are even in different cities. This will further hinder the process of assistance. 3) the lack of assistance by volunteers also has an impact on the interaction of deaf students with lecturers and deaf students with regular students during online learning. This is because not all lecturers can communicate using sign language